Serum Folate Status Is Primarily Associated With Neurodevelopment in Children With Autism Spectrum Disorders Aged Three and Under—A Multi-Center Study in China - Li, Qiu; Yang, Ting; Chen, Li; Dai, Ying; Wu, Li-Jie; Jia, Fei-Yong; Hao, Yan; Li, Ling; Zhang, Jie; Ke, Xiao-Yan; Yi, Ming-Ji; Hong, Qi; et al. (Frontiers in Nutrition, 2021)
Background: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder. Folate has been demonstrated to be associated with ASD. However, the current studies of the correlation between folate and symptoms of children with ASD have inconsistent conclusions, are mainly small samples, and lack age-stratified analysis. This study purposed to explore the association between folate and symptoms of autistic children at different age groups from a multi-center perspective. Methods: We recruited 1300 children with ASD and 1246 typically developing (TD) children under 7 years old from 13 cities in China. The Autism Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and Childhood autism rating scale (CARS) were used to evaluate the symptoms of children with ASD. China neuropsychological and Behavior Scale-Revision 2016 (CNBS-R2016) scale was conducted to evaluate the neurodevelopment of children with ASD. Serum folate was measured by chemiluminescence assay in the two groups. Results: The serum folate levels of children with ASD were lower than that of TD children. In terms of core symptoms of ASD, we found that the serum folate levels were not associated with ABC, SRS and CARS scores in ASD children of all ages but negatively associated with communication warning behavior scores of CNBS-R2016 in ASD children aged 3 and under. Concerning development quotients, it was at the age of 3 and under that serum folate levels were positively associated with gross motor, fine motor, language and general quotient of ASD children. These ASD children aged 3 and under were further divided into two groups according to the median of serum folate (14.33ng/ml), we found that compared to ASD children with folate ≤ 14.33ng/ml, those with folate >14.33ng/ml had lower communication warning behavior score and higher gross motor, fine motor, adaptive behavior, language, person-social, and general development quotients. Conclusion: We found that folate status was primarily associated with the neurodevelopment of children with ASD aged 3 and under. Besides, relatively higher serum folate levels may be more beneficial for children with ASD.